Data on the effects of increase in water colour on lake plankton communities - Lindström, Eva S. (Uppsala University, 2017)
Increases in water colour (brownification) have been observed in aquatic systems in the Northern Hemisphere, partly caused by increased loading of organic carbon from terrestrial origins. We investigated the effect of increase in water colour on the composition, structure and function of lake plankton communities (bacteria, phytoplankton and zooplankton) conducting a mesocosm experiment. Experiments were performed during the summer of 2013 in 3 lakes — Ekholmssjön (59° 52’ 45’’ N, 18° 32’ 11’’ E), Hålsjön (59° 49’0’’ N, 17°13’46’’ E) and Edasjön (59°48’ 15’’ N, 17° 54’8’’ E) — located in central Sweden. The lakes were chosen to be representative of boreal forest lakes (e.g. relatively small, meso-humic and mesotrophic). Although the lakes were meso-humic, they are in the medium range of DOC concentration and water colour in the study region and are prone to be affected by brownification.

See article "Increased water colour affects freshwater plankton communities in a mesocosm study" by Lebret et al (2018) for further information.

The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk version av denna katalogpost för information om dataset och insamling.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data on the effects of increase in water colour on lake plankton communities
Increased water colour affects freshwater plankton communities but not ecosystem functions in a mesocosm study
Keywords: lakes; sjöar; plankton; plankton; Ecology; Ekologi